The Dancer and the Dance : A Book of Distinctions - Foley, Jack (Book collections on Project MUSE., 2012)
Jack Foley's The Dancer and the Dance: A Book of Distinctions deliberately challenges many conventional ways of thinking about poetry. Though extremely scholarly and aware of the "tradition," Foley offers readings rooted in a consciousness which is simultaneously non-academic and open to the new. "The self of this book," he writes, "is not a unity but a multiplicity. Many people would agree with this idea of selfhood-the self as a 'multiplicity of voices'-but clarification is still required as to how the concept of the self as multiplicity affects literary criticism, how it affects our actual reading of poems. It may be that the self we postulate as we read a poem contradicts the self we experience in the world; it is also possible that familiar poems may be experienced anew by being read in the light of multiplicity." Foley's explorations lead him into radically new readings of "canonic" work by poets such as Keats, Yeats and Mallarme, into the world of opera, free jazz, New Formalism and the writing of song lyrics, into "ethnic" literature, theater and finally into problems of "spoken word" and "slam poetry." Throughout, his point of view, initially controversial, becomes finally compelling. "It is possible," he says quietly about the whole of Western culture, "that Plato was wrong, and that we must make an effort to think in a different way if we are to encounter reality at all."